Genetic Diversity of Mahseer (Tor spp.) in Jambi: A DNA Barcoding Approach for Conservation - Nazifa, Boti Iffa; Sulistiono; Mashar, Ali; Sukmono, Tedjo (Al-Kauniyah: Jurnal Biologi, 2026)
Genetic-based management is a critical approach to maintain the sustainability of mahseer fish (Tor tambra and T. tambroides), which are facing threats from habitat degradation and overfishing in Jambi Province. This study aims to analyze the genetic diversity and population structure of mahseer using the COI gene markers. A total of 18 specimens were collected from six locations in the Jambi rivers (June-August 2024). DNA sequencing results showed 98.51–99.85% similarity to the references T. tambra and T. tambroides in GenBank. Phylogenetic analysis confirmed the grouping of this species, with a bootstrap value of 100% and closeness to the species Barbonymus gonionotus and Hampala macrolepidota. There were 11 haplotypes with the highest diversity at stations 3 and 6 (Hd= 0.90000), while moderate genetic differentiation (Fst= 0.109–0.141) was found between station 2 and other locations, indicating isolation due to habitat fragmentation. Water quality parameters (dissolved oxygen 6.3–7.1 mg/L, pH 7.0–7.3, current velocity 0.2–0.4 m/s) support habitat suitability, but anthropogenic activities potentially threaten genetic connectivity. These findings underscore the need for genetic data-driven conservation strategies, such as restocking of highly diverse populations and protection of critical habitats. Further research is needed to monitor long-term genetic dynamics.